Analisis Kesulitan Siswa dalam Menyelesaikan Soal Cerita SPLDV Ditinjau dari Motivasi Belajar - Ratih Pitria Nurazizah; Tatang Herman; Aan Hasanah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to describe the difficulties faced by ninth-grade students at a junior high school in Bandung while tackling word problem involving Systems of Linear Equations in Two Variables (SPLDV) and to examine how these difficulties are associated with their learning motivation. The research employed a descriptive qualitative approach, engaging 35 students who completed a diagnostic test. Based on the test results, three students representing high, medium, and low motivation levels were randomly selected for interviews to validate and further explore the challenges they encountered. Data collection involved a problem-solving test developed based on Polya’s steps, along with in-depth interviews. Findings reveal that highly motivated students were generally able to complete most stages, although difficulties still occurred in the planning phase. Students with moderate motivation commonly struggled with understanding the problem and determining an appropriate plan. In contrast, students with low motivation encountered obstacles in nearly all of Polya’s stages, particularly in comprehending information, identifying variables, and verifying their answers. These result support previous studies suggesting that learning motivation influences students’ problem-solving strategies and accuracy when working on mathematical tasks. Overall, learning motivation contributes significantly to the quality of students’ thinking processes in solving SPLDV word problems.